Oral Health Status and Oral Impact on Daily Performance in Elderly in Northeastern Region Thailand - Sombateyotha, K.; Mahaweerawat, U. (European Journal of Sustainable Development, 2017)
The quality of life index as oral impact on daily performance (OIDP) is very significant indicator for people teeth loss or oral health problem in specific socio-cultural community where generalized for assessment. The research is aimed to investigate dental health status and their OIDP for the elderly. This cross-sectional descriptive study was comprised of seven provinces by randomized selected in Northeastern region of Thailand, with 2,939 elderly. All those elderly were dental health examined and interviewed by using standardized questionnaire included dental health behavior, psychological health and OIDP form. This results showed that the OIDP scoring 5 level, first 3 of 5 level ranking is the most severity level magnitude such as eating food (52.2%), speaking (51.9%), embarrassed by teeth appearance (51.9%), which affected daily life performances. The statistical analysis showed that subjects perceived their irritation in oral cavity [adjusted odds ratio (AOR)=2.11; 95%CI=1.62-4.31], xerostomia [AOR=1.89; 95%CI=1.02-3.13], restricted their sugar consumption [AOR=2.38; 95%CI=1.22-3.80], low frequency of cleaning teeth [AOR=1.96; 95%CI=1.09-3.03], visited a dentist during the past three years or more [AOR=2.89; 95%CI=1.20-4.15]. In conclusions, the high prevalence of oral hygienic problem with OIDP also still high magnitude level. Thus community oral health education programs and dental skill training need to be improved and fulfilled. Keyword: Oral impact on daily performance (OIDP), elderly, oral health